FREQUENCIES OF CONGENITAL ANOMALIES AMONG NEWBORNS ADMITTED IN NURSERY OF AYUB TEACHING HOSPITAL ABBOTTABAD, PAKISTAN - Gillani, Saima; Kazmi, Nasir Hussain Shah; Najeeb, Shahzad; Hussain, Saad; Raza, Ali (Journal of Ayub Medical College Abbottabad, 2011)
Background: Congenital anomalies play a significant role in perinatal and neonatal morbidity and mortality. The frequency of these congenital anomalies varies in different populations. Objective of this study was to find out the frequencies of congenital anomalies admitted in nursery of Ayub Teaching Hospital, Abbottabad. Methods: In this descriptive, cross-sectional study all patients admitted in NICU from October 2009 to January 2010 were included. The patients were examined for major and minor congenital anomalies. The observations were recorded in tabulated form. Results: A total of 2,360 patients were admitted in NICU during the study period. One hundred patients were noted to have congenital anomalies. The most frequent anomalies involved the central nervous system (31%). Meningomyelocele was the commonest defect (71%, 22 out of 31 cases of CNS defects), among these males were more (77%, 17 out of 22 of meningomyelocele cases) than females (14 out of 31). These were followed by patients born with congenital heart defects (16%). Patients with urogenital anomalies (6%) were all male except for one who had ambiguous genitalia. Conclusions: Cases of meningomyelocele were the commonest presenting congenital anomaly. More stress should be laid on the role of peri-conceptional vitamin supplementation like folic acid for the primary prevention of congenital defects. Keywords: congenital anomaly, birth defect, encephalocele, anencephaly, Down's syndrome, trisomy